Factors That Influence Student Interest in Choosing Private Universities in Bandar Lampung - Sinaga, Martha Alfreda; Rahayu, Ni Putu Widhia (LPPPIPublishing, 2023)
The number of students in private universities in Bandar Lampung has fluctuated. This study aims to examine the effect of college image on student involvement and student loyalty, then to examine the effect of relationship quality on student involvement and student loyalty, finally to examine the effect of student involvement on student loyalty. This research uses a quantitative approach. Data were collected through an online questionnaire using a Likert scale, a population of 174, purposive sampling technique, the sample determined by the Slovin formula was 63. Data analysis used multiple linear tests with the help of SPPS version 20 and also conducted hypothesis tests such as the t test and F test. The findings show that there is a positive and significant effect of college image and relationship quality on student involvement and there is an effect of relationship quality on student involvement and student loyalty as well as a significant effect of student involvement on student loyalty but image has no significant impact on student loyalty. The results of the mediation variable show that the image mediated by student involvement has an influence on student loyalty while student involvement does not mediate the effect of relationship quality on student loyalty.